Pengaruh Pengungkapan Environmental, Social, dan Governance (ESG) terhadap Nilai Perusahaan Sektor Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024 - Sarumaha, Sipriana Etlis Anastsya; Andayani, Wuryan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This quantitative study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure on the value of consumer goods companies listed on the Indonesia Stock Exchange during the 2021-2024 period. Using purposive sampling, 25 companies were selected as the research sample, resulting in 100 observations. Secondary data in the form of annual reports and sustainability reports were analyzed using multiple linear regression with IBM SPSS Statistics. The results indicate that environmental disclosure has no effect on firm value, social disclosure has no effect on firm value, and governance disclosure has no effect on firm value. These findings suggest that ESG information has not been fully considered by investors in their valuation decisions and that sustainability disclosure is still perceived as a short-term cost burden. Therefore, ESG disclosure in the consumer goods sector has not yet been able to provide added value reflected in firm value.